Transperineal Repair of Secondary Perineal Hernia Using a Mesh with a Memory-recoil Ring - Katsuhito Suwa; Takanori Kurogochi; Takuro Ushigome; Hiroya Enomoto; Tomoyoshi Okamoto; Ken Eto (Journal of the Anus, Rectum and Colon, 2023)
Objectives: The aim of this study was to evaluate the effectiveness of transperineal repair of secondary perineal hernia (SPH) using a mesh with a memory-recoil ring. Methods: Seven patients with SPH who underwent transperineal repair (TPR) between July 2010 and May 2022 were retrospectively analyzed. TPR was performed using a mesh with a memory-recoil ring. Results: All SPHs developed after abdominoperineal resections in patients with anorectal malignancies. The median longitudinal and transverse diameters of the hernia orifice were 8 (7-10) cm and 6 (5-7) cm, respectively. In all cases, the mesh was fixed to the ischial tuberosity, residual levator muscle, coccygeus muscle, and coccyx after thorough dissection of the sac. The median operation time was 154 (142-280) min. Perioperative complications occurred in 2 cases (29%). One was enterotomy, which caused postoperative mesh infection requiring extraction of the mesh. The other was vaginal injury, which resulted in vaginal fistula but closed spontaneously. The median postoperative length of stay was 9 (5-14) days. No recurrence was observed during a median follow-up of 35 (9-151) months. Conclusions: TPR using a mesh with a memory-recoil ring is safe, feasible and promising technique for SPH repairs.